A velhice e o envelhecimento: seus significados na vida de um grupo de jornalistas com mais de 60 anos de idade - Pagenotto, Maria Lígia Mathias (2011)
This study aims to discuss old age and aging as personal condition and sociocultural process. It focuses on the passage of time in people‟s life, considering the articulation of chronological time and kairos time. The researcher who has been a journalist since the 1980s interviewed six journalists with the written press of the city of São Paulo; firstly, with the purpose of analyzing, through the testimonies and her own experience, the relationship between these communication professionals and the way they age in the professional environment; secondly, in order to understand in a broader way the meanings of old age and aging in the social context. In the case of Journalism, in the 1980s and 1990s, the researcher could witness, in the condition of a novice in the area, remarkable events in the history of the press in Brazil, not only from the political point of view (post-dictatorship), but also from the technological standpoint, with a series of changes in the printed media sector, especially with the inclusion, in large newspaper companies, of digital machines, and, consequently, with the replacement of many editing professionals in a broader way. The tensions of that moment were observed in her working environment, and they led her to think for the first time about her aging and that of the group in which she was entering as a novice. A group of journalists that was divided in a sharp way, mainly due to the difference in generations that of the younger journalists (between 25 and 40 years of age) and that of the older journalists (50 years and older). In addition, the researcher could take a close look on how the journalists, mainly the older ones, dealt with the imposition of new technological equipment in the newsrooms and how they were seen and treated when they were not familiarized with the new working tools. As investigation strategy, a qualitative methodology was used, with semi-structured interviews directed at these six professionals, who were freely chosen by the researcher. The only criterion that was followed was that of interviewing people who are active in their professional career of journalist and aged 60 or older - the elderly person standard established by the UNO (United Nations Organization)